SPORT AND EMPLOYMENT IN EUROPE: THE STATUS OF PHYSICAL EDUCATION IN PORTUGAL (Fiep Bulletin - online, 2013)
This study is supposed to study the job offers in physical education, specifically speaking, public teaching, being done by comparing the number of graduated college students, private and public and the number teachers placed in public teaching. As part of the sample are establishments of higher education (32), University (10) and Polytechnic (22). Teachers who applied to teaching group posts 260 and 620 from 2004/2005 till the school year of 2006/2007, where also analyzed. The results indicate that the number of subscribers students in higher education decreased over time, the number students who are graduates annually, in higher education and enter the labor market, particularly in the teaching of Physical Education, remained decreased slightly. Finally, the number of teachers that is placed in School Education, note a steady increase, but more significant in the year 2006/2007 (55.2%). When analyzed all the results, we concluded that the number of deployed, and not placed outside the competition for teachers, increases from year to year. Despite the decrease of subscribers students and graduates, the waiting lists for placement are still high (6.314). Analyzing this fact, given that the labor market is exhausted, but may be showing signs of head to balance, thus increasing the possibility of employment.
Keywords: Higher Education; Graduated; Placed Teachers